1976
DOI: 10.1785/bssa0660051713
|View full text |Cite
|
Sign up to set email alerts
|

Microearthquake survey of Tehran region, Iran

Abstract: A short microearthquake survey of part of north central Iran around the city of Tehran made late in 1974, showed that earthquakes occurred at the rate of 21.37 events per day. Epicentral locations for 37 events, using a geometric ray path technique, show the observed activity to be concentrated in three principal groups: two associated with the known major fault on the south flank of the Alborz mountain, while the third constitutes a previously unrecognized lineation passing very close to the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The analysis of a dense network of GPS sites covering Central Alborz (Djamour et al, 2010) has revealed important kinematic aspects of the present-day deformation. For the faults south of the range (Mosha, Firuzkuh, and Astaneh), the vertical component of faulting is not significant, consistent with the fact that the faults are mainly left-lateral (e.g., Hedayati et al, 1976;Trifonov et al, 1996;Jackson et al, 2002;Allen et al, 2003;Hessami et al, 2003;Ashtari et al, 2005;Nemati et al, 2011;Solaymani Azad et al, 2011). At the northern border, the Khazar Fault which is suggested as the tectonic boundary between Alborz and the South Caspian Basin (e.g., Berberian et al, 1983), is divided into two distinct portions: (1) the western segment is mainly a thrust fault slipping at ∼6 mm/yr, with a left-lateral component of ∼2-3 mm/yr; (2) the eastern segment is predominately left-lateral (∼5 mm/yr) accompanied with a lesser component of thrust faulting at ∼2-3 mm/yr.…”
Section: Introductionsupporting
confidence: 53%
“…The analysis of a dense network of GPS sites covering Central Alborz (Djamour et al, 2010) has revealed important kinematic aspects of the present-day deformation. For the faults south of the range (Mosha, Firuzkuh, and Astaneh), the vertical component of faulting is not significant, consistent with the fact that the faults are mainly left-lateral (e.g., Hedayati et al, 1976;Trifonov et al, 1996;Jackson et al, 2002;Allen et al, 2003;Hessami et al, 2003;Ashtari et al, 2005;Nemati et al, 2011;Solaymani Azad et al, 2011). At the northern border, the Khazar Fault which is suggested as the tectonic boundary between Alborz and the South Caspian Basin (e.g., Berberian et al, 1983), is divided into two distinct portions: (1) the western segment is mainly a thrust fault slipping at ∼6 mm/yr, with a left-lateral component of ∼2-3 mm/yr; (2) the eastern segment is predominately left-lateral (∼5 mm/yr) accompanied with a lesser component of thrust faulting at ∼2-3 mm/yr.…”
Section: Introductionsupporting
confidence: 53%